Keuntungan dan Tantangan dalam Penggunaan Akad Mudharabah untuk Pembiayaan Usaha Mikro, Kecil, dan Menengah (UMKM) - Tiur Herlina Yanti Hutagalung; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
There are various types of financing in Islamic banking or financial institutions, one of which is mudharabah financing. This financing is a cooperation agreement between the capital owner (shohibul mal) and the fund manager (mudharib) for a business, where the profit is shared according to the agreed percentage based on the profit obtained. Mudharabah financing is closely related to UMKM, where UMKM owners, especially housewives, play an important role in managing family finances. This study aims to examine what are the challenges for UMKM in using the mudharabah contract and what are the advantages of using the mudharabah contract. The method used in this study is qualitative research with a descriptive approach, as well as descriptive data analysis through literature studies from scientific journals and books. The results of this study indicate that mudharabah financing can help the community in improving UMKM.